Short bowel syndrome: treatment options - Eça,Rosário (2016)
ABSTRACT Introduction: Short bowel syndrome (SBS) refers to the malabsorptive state that occurs following extensive intestinal resection and is associated with several complications. Methods: The research for this review was conducted in the Pubmed database. Relevant scientific articles dated between 1991 and 2015 and written in Portuguese, Spanish or English were selected. Results: Several therapies, including nutritional support, pharmacological options and surgical procedures have been used in these patients. Conclusions: Over the last decades new surgical and pharmacological approaches emerged, increasing survival and quality of life (QoL) in patients with SBS. All SBS patients ought to have an individualized and multidisciplinary care that promotes intestinal rehabilitation.